2019
DOI: 10.1021/acs.energyfuels.9b00755
|View full text |Cite
|
Sign up to set email alerts
|

Production of Aryl Oxygen-Containing Compounds by the Pyrolysis of Bagasse Alkali Lignin Catalyzed by LaM0.2Fe0.8O3 (M = Fe, Cu, Al, Ti)

Abstract: A series of LaM0.2Fe0.8O3 (M = Fe, Cu, Al, Ti) samples synthesized by the sol–gel method were used to catalyze the pyrolysis of bagasse alkali lignin (BAL) to produce aryl oxygen-containing compounds. The effects of doping metal ions in the B-site of LaFeO3 were investigated by X-ray diffraction, scanning electron microscopy, Brunauer–Emmett–Teller, and X-ray photoelectron spectrometer. Furthermore, the catalytic pyrolysis performances of the perovskites were evaluated by thermogravimetric analysis and the fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The lattice spacing of 0.272–0.274 nm (Figure f) for LFO material corresponds to the crystal planes of LaFeO 3 (110) (PDF no. 97-002-9234) . The different lattice spacings of 0.284, 0.335, and 0.452 nm were interconnected in LFAO-3 (Figure g), which indicated that Al doping caused lattice distortion …”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The lattice spacing of 0.272–0.274 nm (Figure f) for LFO material corresponds to the crystal planes of LaFeO 3 (110) (PDF no. 97-002-9234) . The different lattice spacings of 0.284, 0.335, and 0.452 nm were interconnected in LFAO-3 (Figure g), which indicated that Al doping caused lattice distortion …”
Section: Resultsmentioning
confidence: 91%
“…The generation of the concomitant peak splitting and the change in electron binding energy reflect the ability of the O 2p electron to afford La, i.e., they reflect the covalent nature of La–O. With the increasing Al-doped content, the electron binding energy of La 3d tends to increase (0.3–0.8 eV), which indicates that when the covalent nature of La–O decreases, lattice oxygen may participate in phosphate adsorption. , With increasing Al-doped content, the electron binding energies of Al 2p (Figure c) and Fe 2p (Figure d) tend to increase and decrease, respectively; Al doping may cause a change in the Fe valence state . The XPS spectra of the Fe 2p region can be fitted into peaks at ∼708.7–710.5 and 723–724 eV belonging to Fe 2+ and at 710.5–712.6 and 724.8–725.9 eV belonging to Fe 3+ (Figure d). ,, After doping with Al, the ratio of Fe 2+ /Fe 3+ tends to increase, indicating that additional Fe 3+ is converted to Fe 2+ (Table S2), which may generate oxygen vacancies and adsorb oxygen on the surface because of charge compensation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Rapid pyrolysis of biomass is one of the most promising methods to convert abundant biomass into bio-oil. Bio-oil has a high oxygen content, low calorific value, poor stability, and high corrosiveness, which means that it cannot directly replace petroleum products. Therefore, various catalysts and additives have been tested during biomass pyrolysis, in order to improve the quality of the bio-oil products through a series of deoxygenation reactions. , …”
Section: Introductionmentioning
confidence: 99%